Prospective cohort study showing changes in the monthly incidence of Pneumocystis carinii pneumonia. Issue 929 (1st March 2003) - Lubis, N; Baylis, D; Short, A; Stebbing, J; Teague, A; Portsmouth, S; Bower, M; Nelson, M; Gazzard, B
Abstract : Pneumocystis carinii pneumonia (PCP) remains a serious opportunistic infection in HIV infected individuals. Seasonal changes in climate are associated with changes within individual susceptibility to infection. The possibility of monthly variability in the incidence of PCP was therefore examined by means of a cohort study of a database of 8640 HIV infected individuals attending the Chelsea and Westminster Hospital. There were 792 cases of PCP diagnosed since 1985. A marked decline was observed in the incidence of PCP in mid-1992 coincident with the introduction of PCP prophylaxis. There was a further decline in 1996 after the introduction of highly active antiretroviral therapy. Despite no significant monthly variation in the mean attendance to clinic and CD4 count, both new and all cases of PCP were higher in January than in other months (15.9% and 14.5% of all cases, respectively). A correlation with low rainfall in January and new cases of PCP was observed. These data are consistent with an influence of climatic conditions on the presentation of PCP. The diagnosis of PCP is more common in winter months suggesting that this is a transmissible infection.